2010
DOI: 10.1152/ajprenal.00426.2009
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ACE2 and angiotensin-(1–7) in a mouse model of early chronic kidney disease

Abstract: Angiotensin-converting enzyme 2 (ACE2) is expressed at high levels in the kidney and converts angiotensin II (ANG II) to ANG-(1-7). We studied the effects of ACE2 inhibition and ANG-(1-7) in the (5/6) nephrectomy ((5/6) Nx) mouse model of chronic kidney disease (CKD). Male FVB mice underwent sham surgery (Sham) or (5/6) Nx and were administered either vehicle, the ACE2 inhibitor MLN-4760 (MLN), the AT(1) receptor antagonist losartan, MLN plus losartan, or ANG-(1-7) for 4 wk. In (5/6) Nx mice with or without ML… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
103
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(108 citation statements)
references
References 40 publications
4
103
1
Order By: Relevance
“…Sukumaran et al suggested that telmisartan provided beneficial protection against heart failure in rats, at least partly by suppressing inflammation, oxidative stress, and endoplasmic reticulum stress, as well as through modulation of the ACE2/Ang (1-7)-Mas axis [23] . Moreover, kidney ACE2 was shown to be downregulated in a mouse model of early chronic kidney disease [24] , whereas AT1-R antagonism of early radiation-induced changes in microglial activation or neurogenesis in normal rat brains has not been reported [25] . This discrepancy may be relevant to differences in disease conditions, the tissues involved, or the variety of ARB drugs tested.…”
Section: Discussionmentioning
confidence: 99%
“…Sukumaran et al suggested that telmisartan provided beneficial protection against heart failure in rats, at least partly by suppressing inflammation, oxidative stress, and endoplasmic reticulum stress, as well as through modulation of the ACE2/Ang (1-7)-Mas axis [23] . Moreover, kidney ACE2 was shown to be downregulated in a mouse model of early chronic kidney disease [24] , whereas AT1-R antagonism of early radiation-induced changes in microglial activation or neurogenesis in normal rat brains has not been reported [25] . This discrepancy may be relevant to differences in disease conditions, the tissues involved, or the variety of ARB drugs tested.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, no aggravation of renal injury produced by kidney ischemia-reperfusion was observed in Mas K/K mice, and in the same model the Mas agonist AVE 0991 reduced renal injury (Barroso et al 2012). Ang-(1-7) was also reported to stimulate (Burns et al 2010) or to inhibit ) the epithelial-to-mesenchymal transformation in tubular cells.…”
Section: Vascular Actions Of the Ace2/ang-(1-7)/mas Axismentioning
confidence: 90%
“…It is important to highlight that the ACE levels were notably increased in this study (Soler et al 2007). Moreover, ACE2 was downregulated in the cortex of mice subjected to subtotal nephrectomy (Dilauro et al 2010). Administration of recombinant ACE2 diminished fibrosis, i.e.…”
Section: Vascular Actions Of the Ace2/ang-(1-7)/mas Axismentioning
confidence: 98%
See 1 more Smart Citation
“…69 -72,74 -78 ANG II, CTGF, AND SIGNALING PATHWAYS Initially, CTGF was mainly understood to act downstream of TGF␤ to regulate ECM synthesis. 4,8 The Smad proteins are essential components of this intracellular signaling pathway, acting as transcription factors for TGF␤-mediated responses, including fibrosis. 73 In a rat model of remnant kidney disease, Ang II induces tubular mRNA encoding CTGF and collagen I, and the subsequent proteins are upregulated by phosphorylated Smad2/3 but downregulated by Smad7; that is, overexpression of Smad7 abolishes Ang IIinduced Smad2/3 phosphorylation and upregulation of CTGF and collagen I.…”
Section: Ang II and Ctgfmentioning
confidence: 99%